Standarisasi Pesantren: Upaya Peningkatan Mutu Pesantren Secara Berkelanjutan - Nurcholiq, Mochamad; Ahmad Zamzami; Siti Mutholingah (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2024)
This research aims to examine the importance of standardization in improving the quality of Islamic boarding school education and finding the ideal format for quality Islamic boarding schools in a sustainable manner. A literature study was conducted to examine various factors that influence the success of standardization, including internal and external factors in Islamic boarding schools. The research results show that standardization plays a crucial role in realizing Islamic boarding school education that is quality, sustainable and relevant to the demands of the times. Standardization not only guarantees the quality of learning, but also increases the accountability and credibility of Islamic boarding schools in the eyes of the community. The ideal format for a quality Islamic boarding school that can meet the demands of today's era is the integration of Salaf education with formal education at the Islamic boarding school